The Influence Of Working Capital Financing And Consumptive Financing Of Islamic Commercial Banks On Economic Growth - Nabila Aretha Putri Yunaz; Haqiqi Rafsanjani; Dian Berkah (UNIVED Press, 2025)
Economic growth is a main indicator in assessing the development of a country, which is influenced by various factors, including financing distributed by Islamic banking. This research aimed to analyze the influence of working capital financing and consumptive financing by Islamic commercial banks on economic growth in Indonesia. The method used a quantitative approach with the Vector Error Correction Model (VECM) model to analyze the short-term and long-term relationship between the variables of working capital financing, consumptive financing, and economic growth. The data used monthly time series data from the official reports of the Financial Services Authority and the Indonesian Central Statistics Agency for the 2014–2023 period which is processed using Eviews 13. The results showed that consumptive financing had a significant influence on economic growth in the short term. However, the impact is not long-lasting and tends to subside in the long term. In contrast, working capital financing has no direct influence on economic growth in the short term, but in the long term it showed that a stronger linkage to economic growth through increased productivity and investment. This research showed that although consumptive financing can drive economic growth in the short term through increased consumption, the impact is less sustainable compared to working capital financing which contributes more to long-term economic growth. Therefore, the optimization of working capital financing in Islamic banking needed to be increased to support more stable and sustainable economic growth.